Status of the Northern Pintail Anas acuta (Anseriformes: Anatidae) in Sumatra - Abdillah, Hasri (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2025)
The Northern Pintail Anas acuta is a migratory waterfowl species that passes through Indonesia during its annual migration. This study reports on the presence of A. acuta in northern Sumatra, Indonesia, based on recent observations and historical records. Our results show that there are four records of A. acuta in Sumatra, with three records in 2012 and 2020, from Percut, North Sumatra. The consistency of records from this location suggests that it may provide suitable habitat for the species. The presence of A. acuta in Sumatra is a rare but regular visitor. Keywords: Anas acuta, East Asian-Australasian Flyway, migration, Northern Pintail, waterfowl.